The Perspective of Human Rights and Criminal Law in Viewing the Criminal Law Policy on Chemical Castration Sanctions in Indonesia - Darlisma Darlisma (LEGAL BRIEF, 2022)
Sexual violence is one of the most severe crimes and is part of human rights violations. Especially when children become victims of this crime. Therefore, the government issued a regulation regarding the provision of sanctions for perpetrators of sexual violence, especially against children. This study aims to see the views of human rights and criminal law in Indonesia in implementing the criminal law of chemical castration sanctions for perpetrators of sexual violence. This research will be carried out using a normative juridical approach. The data that will be used in this research come from different research results, previous studies, and laws that are relevant to this research. The results of this study found that the provision of castration law is something that is considered vile and inhumane. This is because this punishment can make the perpetrator lose confidence in returning to the community so that it is not following the purpose of the law, which seeks to maintain solidarity in the community.